2002
DOI: 10.2190/12b7-rag9-9qur-61k6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prior Knowledge, Attitudes, Ability, and Activity Structure on Students' Learning and Use of Software

Abstract: Based on evidence from the learner control literature, a study was designed that aimed to identify the conditions and individual characteristics that would best support learners' acceptance of control within hypermedia. The effects of prior domain knowledge, learning activity structure, ability, and attitudes on acceptance of control opportunity, knowledge acquisition, and attitudes were investigated. The study was conducted in two single-gender schools to remove the effects of gender interaction while using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Contextual factors-such as age, gender, learning style, degree programmes and previous knowledge of computers-assumed to influence students' perceptions (Mitra et al, 2000;Nachmias & Shany, 2002) were found to exert minor influence. This result has been verified in other studies (Lu et al, 2002;Tolhurst & Debus, 2002) and suggests a strong need for closer study of models of implementation and an exploration of their underlying theoretical frameworks.…”
Section: Introductionsupporting
confidence: 74%
“…Contextual factors-such as age, gender, learning style, degree programmes and previous knowledge of computers-assumed to influence students' perceptions (Mitra et al, 2000;Nachmias & Shany, 2002) were found to exert minor influence. This result has been verified in other studies (Lu et al, 2002;Tolhurst & Debus, 2002) and suggests a strong need for closer study of models of implementation and an exploration of their underlying theoretical frameworks.…”
Section: Introductionsupporting
confidence: 74%
“…McIntyre and Wolff (1998) mentioned that "One of the interaction forces in a web environment is the ability to capture, providing quick and imperative interaction and feedback to the students". It is worth mentioning that some studies used the technology acceptance model in initial or extended version (Ong, Lai, &Wang, 2004;Drennan, Kennedy, & Pisarki, 2005;Saadé & Bahli, 2005;Ngai, 2007), while other studies depended on statements of teams that are focus on the added value and the level of computer use in education (Mitra, Lenzmeier, Steffensmeier, Avon, Qu, N., Hazen, 2000;Shuell & Farber, 2001) and other studies used literature model that are related to the online meetings (Bures, Amundsen, & Abrahmi, 2002) and the use of hypermedia (Tolhurst & Debus, 2002).…”
Section: Information Technology (Variable α3)mentioning
confidence: 99%
“…Keller and Cernerud [2002] found the degrees of perceived usefulness and ease of use among students to be highly dependent on organizational factors connected to the implementation of the virtual learning environment. Tolhurst and Debus [2002] concluded that students' acceptance of online learning was influenced by epistemological belief inherent in the school culture and gender. Legris et al [2003], in a critical review and meta-analysis of the TAM, concluded: -TAM is a useful model, but has to be integrated into a broader one, which would include variables related to both human and social change processes, and to the adoption of the innovation model‖ [Legris et al 2003, p. 191].…”
Section: Introductionmentioning
confidence: 99%